A Survey of Perceptions and Practices of Complementary Alternative Medicine among Canadian Gastroenterologists - Zane Gallinger; Brian Bressler; Shane M Devlin; Sophie Plamondon; Geoffrey C Nguyen (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Despite a high prevalence of complementary alternative medicine (CAM) use among inflammatory bowel disease (IBD) patients, there is a dearth of information about the attitudes and perceptions of CAM among the gastroenterologists who treat these patients.